UPAYA PENINGKATAN MANAJEMEN SUMBER DAYA MANUSIA DI TK AR-RAIF, KALASAN SLEMAN, YOGYAKARTA - Aulia Rahma (QURROTI, 2020)
Improving human resource management is a continuous process that aims to improve the quality of people in an organization. The purpose of this study was to determine the improvement of human resource management in Kindergarten Ar-Raif, Kalasan Sleman, Yogyakarta. This research is a qualitative descriptive study with data collection methods in this study using observation, interviews and documentation. As for the methods/efforts used to develop human resources in the school, namely by holding coaching, workshops, training, comparative studies, providing facilities and infrastructure that can support learning activities, and so on. In terms of improving human resource management at Kindergarten Ar-Raif, Kalasan Sleman, Yogyakarta, it is good enough, this can be seen from the well-organized academic atmosphere.